Bacterial pathogens and in-hospital mortality in revision surgery for periprosthetic joint infection of the hip and knee: analysis of 346 patients - Migliorini, Filippo; Weber, Christian David; Bell, Andreas; Betsch, Marcel; Maffulli, Nicola; Poth, Vanessa; Hofmann, Ulf Krister; Hildebrand, Frank; Driessen, Arne (European Journal of Medical Research, 2023)
Introduction: The management of periprosthetic joint infections (PJI) of the lower limb is challenging, and evidence-based recommendations are lacking. The present clinical investigation characterized the pathogens diagnosed in patients who underwent revision surgery for PJI of total hip arthroplasty (THA) and total knee arthroplasty (TKA). Methods: The present study follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). The institutional databases of the RWTH University Medical Centre of Aachen, Germany, were accessed. The OPS (operation and procedure codes) 5–823 and 5–821 and the ICD (International Statistical Classification of Diseases and Related Health Problems) codes T84.5, T84.7 or T84.8 were used. All patients with PJI of a previous THA and TKA who underwent revision surgery were retrieved and included for analysis. Results: Data from 346 patients were collected (181 THAs and 165 TKAs). 44% (152 of 346 patients) were women. Overall, the mean age at operation was 67.8 years, and the mean BMI was 29.2 kg/m2. The mean hospitalization length was 23.5 days. 38% (132 of 346) of patients presented a recurrent infection. Conclusion: PJI remain a frequent cause for revisions after total hip and knee arthroplasty. Preoperative synovial fluid aspiration was positive in 37%, intraoperative microbiology was positive in 85%, and bacteraemia was present in 17% of patients. Septic shock was the major cause of in-hospital mortality. The most common cultured pathogens were Staph. epidermidis, Staph. aureus, Enterococcus faecalis, and Methicillin-resistant Staph aureus (MRSA). An improved understanding of PJI pathogens is important to plan treatment strategies and guide the choice of empirical antibiotic regimens in patients presenting with septic THAs and TKAs. Level of Evidence: Level III, retrospective cohort study.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Arthroplasty; Hip; Infection; Knee; Mortality; Pathogens